Is it possible to continue academic teaching in surgery during the COVID pandemic era?. Issue 4 (1st April 2022) - Arezzo, Alberto; Vignali, Andrea; Ammirati, Carlo Alberto; Brodie, Ronit; Mintz, Yoav
Abstract: In the era of the novel coronavirus (COVID-19) pandemic, we critically appraised the literature by means of a systematic review on surgical education and propose an educational curriculum with the aid of available technologies. We performed a literature search on 10 May 2020 of Medline/PubMed, Embase, Google Scholar and major journals with specific COVID-19 sections. Articles eligible for inclusion contained the topic of education in surgery in the context of COVID-19. Specific questions we aimed to answer were: Is there any difference in surgical education from pre-COVID-19 to now? How does technology assist us in teaching? Can we better harness technology to augment resident training? Two-hundred and twenty-six articles were identified, 21 relevant for our aim: 14 case studies, three survey analyses, three reviews and one commentary. The collapse of the traditional educational system due to social distancing caused a fragmentation of knowledge, a reduced acquisition of skills and a decreased employment of surgical trainees. These problems can be partially overcome by using new technologies and arranging 2-weeks rotation shifts, alternating clinical activities with learning. While medical care will remain largely based on the interaction with patients, students' adaptability to innovation will be a characteristic of post-COVID classes.